Dyspepsia in Early Pregnancy as a Result of Hormonal and Functional Changes: A Case Report - Abitmer Gultom (CV. Inara, 2026)
Introduction: Dyspepsia is a common gastrointestinal complaint in early pregnancy, generally associated with hormonal and functional changes. This condition may reduce quality of life, affect maternal nutritional status, and present a diagnostic challenge in differentiating it from other conditions such as hyperemesis gravidarum or gastrointestinal infection. Case Report: A 27-year-old woman, G1P0A0, at 10 weeks of gestation, presented with nausea and vomiting more than two times per day, accompanied by epigastric discomfort and bloating after meals. Physical examination revealed epigastric tenderness without signs of severe dehydration. Laboratory tests showed normal hemoglobin, mildly elevated leukocytes, slightly decreased potassium, and the presence of bacteria and leukocytes in urine. Result: A working diagnosis of dyspepsia in early pregnancy was established after ruling out hyperemesis gravidarum and gastroenteritis. The patient was treated with Ringer’s lactate infusion, intravenous ondansetron, antacids, and vitamin B complex supplementation, which led to improvement of symptoms. Conclusion: Dyspepsia during pregnancy is a common complaint with both hormonal and functional etiologies. Diagnosis requires thorough history-taking and exclusion of important differential diagnoses. Management should prioritize lifestyle modification and supportive therapy, with safe pharmacotherapy during pregnancy when necessary